The Effect of Health Education on Mandiri Nutrition Management DM Patients at Tamangapa Puskesmas Kelurahan Tamangapa Kecamatan Manggala - Amriati Mutmainna; Indra Dewi (STIKes Patria Husada Blitar, 2022)
Diabetes mellitus is a metabolic disease that can result in pancreatic beta cells unable to produce insulin effectively, resulting in a buildup of blood glucose levels Diabetes is the third largest cause of death in Indonesia with a percentage of 6.7%, after stroke (21.1%) and coronary heart disease (12.9%). One of the control efforts is health education which aims to increase the knowledge of DM patients about independent nutritional management of DM patients. This study aims to develop nursing science, namely information about the effect of health education on independent nutrition management of DM patients at Tamangapa Puskesmas, Tamangapa Village, Manggala District, Makassar City. This type of research used a quasi-experimental research design with a pre-post test design approach. The research has been conducted at the Tamangapa Puskesmas, Tamangapa Village, Manggala District, Makassar City. The population in this study were all patients with Diabetes Mellitus who were undergoing treatment on the day of the study. The samples in this study were 51 people and used total sampling. The results obtained are that there is an effect of health education on independent nutritional management of DM patients at Tamangapa Public Health Center, Tamangapa Village, Manggala District, Makassar City.